2022
DOI: 10.1088/1361-6404/ac6ea1
|View full text |Cite
|
Sign up to set email alerts
|

Lab courses for prospective physics teachers: what could we learn from the first COVID-19 lockdown?

Abstract: At the universities of Dresden, Vienna, and Zagreb, a laboratory course for prospective physics teachers was transferred to an online environment because of the lockdown in March 2020 due to the COVID-19 pandemic. The aim of this paper is to present and compare students’ and instructors’ considerations about the experiences with this laboratory course at these three universities and to formulate guidelines for organizing lab courses for prospective physics teachers. The research was conducted in three steps: f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Because experimental working has been either forbidden or limited during the pandemic, it has been expectedly stated to be a great challenge also in previous research (O’Brien 2021 ; Romadhon et al 2021 ; Nuere and de Miguel 2020 ). We should point it out that Ametepe and Khan ( 2021 ) and Jelicic et al ( 2022 ) have given research-based recommendations for functional online and hybrid laboratory courses, which gives a more positive outlook for the issue. Our finding concerning well-being of the teachers is supported by Klapproth et al ( 2020 ) who have reported that teachers from various school levels have experienced medium to high levels of stress during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because experimental working has been either forbidden or limited during the pandemic, it has been expectedly stated to be a great challenge also in previous research (O’Brien 2021 ; Romadhon et al 2021 ; Nuere and de Miguel 2020 ). We should point it out that Ametepe and Khan ( 2021 ) and Jelicic et al ( 2022 ) have given research-based recommendations for functional online and hybrid laboratory courses, which gives a more positive outlook for the issue. Our finding concerning well-being of the teachers is supported by Klapproth et al ( 2020 ) who have reported that teachers from various school levels have experienced medium to high levels of stress during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…They are related to overburdening the students, lack of technology or familiarity with technology, lack of knowledge of instructional design, and concern about students cheating (e.g., Lemay et al 2020 ; Trust and Whalen 2021 ). Experimental working has been difficult to implement during the pandemic, but it has been substituted with online laboratories, simulations, and homemade experiments, also in the field of physics (Jelicic et al 2022 ; Lemay et al 2020 ; O’Brien 2021 ; Romadhon et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many activities or occurrences around us can be used as learning tools in science education (Abdullah et al, 2014;Abdullah et al, 2020;Aleksandrov et al, 2013;Aslani & Moghiman, 2019;Fallahnezhad & Reza Nazif, 2019;Nelson et al, 2020;Wibowo et al, 2016;Will et al, 2017). Contextual approaches need to be involved instead of textual practices in conducting science learning to become more understandable and fun, especially in physics subject (Dale et al, 2019;Jelicic et al, 2022;Sokolowski, 2021). Through contextual approaches, the learning content that students are studying will look more accurate and easily imagined.…”
Section: Introductionmentioning
confidence: 99%